Republic of Kosovo : First Review Under the Stand-by Arrangement and Request for Modification and Waivers of Applicability of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Kosovo. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses Kosovo's First Review Under the Stand-By Arrangement and Requests for Modification and Waivers of Applicability of Performance Criteria (PC). The program is on track. All end-August 2015 PCs and indicative targets were met by comfortable margins. All structural benchmarks for the first review have been met. More broadly, there is strong ownership of structural reforms in the financial sector and in public procurement. The authorities reaffirmed the targets for the fiscal deficit and bank balances for next year and identified measures to achieve these. The IMF staff support the authorities' request for completion of the first review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet